ANALISIS KEKUATAN OTOT TUNGKAI DAN TENDANGAN SHOOTING KE GAWANG PADA SISWA EKSTRAKURIKULER FUTSAL SMAN 1 BANGKALAN - Sari, Virga Komala; Handayani, Heni Yuli; Purwoto, Septyaningrum Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research began with the author's observation of the many mistakes made by female futsal players when shooting, which resulted in a lack of accuracy and misdirection of the kick. The aim of this research is to analyze the relationship between leg muscle strength and the ability to shoot accurately at the goal. The research method used is a survey method by analyzing leg muscle strength and shooting accuracy with the level of accuracy on goal. The collected data will be analyzed using statistical methods. The research results show that the average result for the vertical jump test is 40 points, while for the shooting accuracy test it is 8 points. For the vertical jump test, there were no female students who were in the very good (0%), good (8%), fair (1%), or very poor (0%) categories. Meanwhile, in the shooting accuracy test, there were no female students who were in the very good category (0%), good (0%), or fair (0%), but there was 1 female student (2%) who was in the very poor category. Based on these results, it can be concluded that both leg muscle strength and shooting accuracy at the goal are in the bad category.